20 years of impact for a food systems transformation: HarvestPlus 2023 annual report - HarvestPlus (International Food Policy Research Institute, 2024)
As we mark the 20th anniversary of HarvestPlus in 2023, I am pleased to share progress towards our mission of addressing hidden hunger in the Global South through biofortification. Our journey to improve nutrition and health is making a difference in the lives of the most vulnerable people. It is heartening to share that in 2023, over 103 million people in farming families across Africa, Asia, and Latin America were eating nutrientenriched foods made from biofortified crops that they grew on their farms, and over 227 million people were accessing through markets. There is additional reach of biofortified crops through organizations like International Potato Center (CIP), The Alliance of Bioversity International and CIAT, and others. In a world where three billion people cannot afford a healthy diet, our work is making a meaningful contribution in providing healthy and affordable nutritious foods to over 330 million people. However, much more needs to be done to enrich food systems and provide access to safe, affordable healthy diets, especially for the most vulnerable people. Through strategic partnerships with public, private, and civil society actors and robust research alliances with CGIAR crop breeding centers and national agricultural research and extension systems (NARES), we have significantly expanded the production and distribution of biofortified crops. By the end of 2023, more than 443 varieties of biofortified crops were released in more than 40 countries, and over 20.7 million farming households were cultivating these varieties on their farms. Our evidence led policy and regulatory reform efforts continue to successfully influence national and regional policies and shape nutrition agendas, leading to an enabling environment for public and private sector investments and support for biofortified crops. This is essential for accelerated uptake, sustainability, and longterm impact. We maintained a focus on ensuring women, adolescent girls, and young children are prioritized and benefit from biofortification, and efforts to increase the economic empowerment of women smallholder farmers and women-led SMEs are gaining momentum. HarvestPlus has also made significant strides in enriching school meal programs with biofortified foods. By incorporating these nutrient-rich crops into school feeding initiatives, we are not only addressing malnutrition but also fostering healthier, more productive futures for children around the world and contributing to nation building. During 2023, HarvestPlus integrated with IFPRI and the wider CGIAR, strengthening our nutrition research, evidence generation, and policy and advocacy efforts. With our crop development partners across CGIAR and national agriculture research systems, we will help facilitate better and more nutritious crop varieties and innovations are developed and released. These innovations will be delivered to our beneficiaries through private and public partnerships including with HarvestPlus Solutions, the scaling arm of HarvestPlus, with a goal of improving the lives and resilience of 1 billion people in the next decade. I extend my sincere gratitude and appreciation to all the members of the HarvestPlus Program Advisory Committee (PAC) as their work comes to an end with the successful integration. The PAC played a critical role in guiding and providing oversight over the last 20 years and placing the HarvestPlus program in this position of strength. This milestone year reflects the dedication and passion of our team members, partners, donors, and supporters. Together, we have made meaningful strides in advancing our mission, for which we are very grateful. The path ahead is full of opportunities to deepen the impact and improve lives of millions more, drive further innovation, and continue our mission to alleviate malnutrition globally.